Molecular detection of Aspergilli from commercial chicken in selected areas of Bangladesh - Arafat, Md Yeasin; Islam, Md Monowarul; Ahamed, Shamim; Mahmud , Md Muket; Rahman, Md Bahanur; Nazir, KHM Nazmul Hussain (Journal of Advanced Veterinary and Animal Research, 2022)
Objectives: This study was designed to isolate, identify, and determine the prevalence of Aspergilli in commercial chicken in selected areas of Bangladesh. Materials and Methods: A total of 50 lung samples from suspected dead chickens, comprising broilers (n = 32) and layers (n = 18), aged between 5 days and 45 weeks, were collected from poultry farms located in the Gazipur district in Bangladesh. Fungi were primarily identified based on the colony morphology using potato dextrose agar (PDA). DNA was extracted from the suspected colonies. Aspergillus spp. was detected by genus-specific ASAP-1 and ASAP-2. Aspergillus spp. were then screened by polymerase chain reaction targeting Aspergillus flavus (FLA-1 and FLA-2), Aspergillus fumigatus (ASPU and Af3r), and Aspergillus niger (ASPU and Nilr). Results: The overall prevalence of Aspergillus spp. was 44% (n = 22/50; p < 0.05). Among the Aspergilli, A. flavus was detected in 10% (n = 5/50) of the samples. Similarly, A. fumigatus and A. niger were detected at 26% (n = 13/50) and 8% (n = 4/50) respectively. Three samples were associated with more than one fungus; two fungi (A. flavus and A. niger) were in two samples, and three fungi (A. flavus, A. fumigatus, and A. niger) were in one sample. Conclusion: Isolation and prevalence of Aspergillus spp. in commercial chicken were studied for the first time in Bangladesh. J. Adv. Vet. Anim. Res., 9(2): 184–190, June 2022 http://doi.org/10.5455/javar.2022.i583